2023
DOI: 10.1002/jmv.29344
|View full text |Cite
|
Sign up to set email alerts
|

Comparing single versus multiple virus detection in pediatric acute gastroenteritis postimplementation of routine multiplex RT‐PCR diagnostic testing

Guy Hazan,
Yoav Goldstein,
David Greenberg
et al.

Abstract: Utilizing multiplex real time polymerase chain reaction (RT‐PCR) for rapid diagnosis of gastroenteritis, enables simultaneous detection of multiple pathogens. A comparative analysis of disease characteristics was conducted between cases with single and multiple viruses. Rotavirus vaccine was introduced in 2010, reaching a 70% coverage in 2 years. All rectal swabs collected from diarrheic children (<5 years) between December 2017 and March 2022 were included. Detection of the same viruses within 2 months was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Prior studies of viral diarrhea in children have suggested that there is greater severity of diarrhea when multiple viruses are detected, but less is known in adults and with bacterial enteropathogens. 31 After adjusting for other factors including age, insurance status, and immunosuppression, detection of multiple pathogens was associated with a 44% increased risk for subsequent ED visits compared to detection of a single pathogen. Those with multiple pathogens were also more likely to receive more than one antibiotic, although overall rates of antibiotic use were similar comparing those with multiple vs. single pathogens.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Prior studies of viral diarrhea in children have suggested that there is greater severity of diarrhea when multiple viruses are detected, but less is known in adults and with bacterial enteropathogens. 31 After adjusting for other factors including age, insurance status, and immunosuppression, detection of multiple pathogens was associated with a 44% increased risk for subsequent ED visits compared to detection of a single pathogen. Those with multiple pathogens were also more likely to receive more than one antibiotic, although overall rates of antibiotic use were similar comparing those with multiple vs. single pathogens.…”
Section: Discussionmentioning
confidence: 93%
“…[26][27][28][29] Hispanic ethnicity may be associated with the detection of multiple pathogens on GI PCR due to a combination of host genetics, geographic location, and socioeconomic factors such as diet, living environment, pathogen exposures, access to medical care, travel, and other social constructs that shape the gut microbiome and influence susceptibility to enteric pathogens. [30][31][32][33][34][35][36][37][38] This study could not determine the specific factors underlying the association between Hispanic ethnicity and higher incidence of multiple pathogens on GI PCR testing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the Netherlands ( Pijnacker et al, 2019 ), Japan ( Hikita et al, 2023 ), and Nepal ( Tandukar et al, 2019 ) demonstrated that co-infection did not increase the risk or severity of AGE. Conversely, a study conducted in Israel indicated that co-infection was associated with more severe clinical symptoms in children under five years old ( Hazan et al, 2024 ). Although the impact of co-infection on the severity of AGE remains unclear, the detection of viral load in stool samples using real-time PCR could be useful in assessing the contribution of individual viruses to the severity of disease as well as virus-virus interaction in co-infection cases ( De Grazia et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%